Pregnancy and neonatal respiratory outcome - Colnaghi, M.; Cognizzoli, P.; Ciuffini, et al., F. (Acta Biomedica Atenei Parmensis, 2012)
Preterm labor is the final common pathway of different complications of pregnancy and despite substantial progress in antenatal care, preterm birth remains a major health issue across the globe. Preterm deliveries in the larger group of spontaneous preterm labor or preterm prelabor rupture of membranes (PPROM) are often associated with intrauterine chorioamnionitis. Current evidence underlines the role of “inflammatory” and “placental dysfunction” disorders in pregnancy on prematurity-associated morbidity, particularly respiratory outcome